La géopolitique interne de l’Equateur après la « révolution citoyenne » - Alexis Sierra (EchoGéo)
The general elections in Ecuador in 2009 closed the first stage of political renovation started by president Rafael Correa. Their analysis show the existence of new political balance between regions while the country have to take up new social and economical challenge.